2012
DOI: 10.1143/jjap.51.08hd01
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Distribution Control of Etching Rate and Critical Dimensions in Microwave Electron Cyclotron Resonance Plasmas for the Next Generation 450 mm Wafer Processing

Abstract: A newly designed microwave electron cyclotron resonance (ECR) plasma etching reactor has been developed for 450 mm wafer processing. The etching rates of polycrystalline silicon (poly-Si) and SiO 2 across the wafer were evaluated as a function of ECR position. Two-dimensional (radial and vertical) distributions of the ion flux in the reactor were also investigated using a movable single probe system. A ring-shaped region of highdensity plasma along the ECR plane was observed. This reveals the mechanism that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Inductively coupled plasmas (ICPs) are widely used in the semiconductor industry [1]. One of the most important concerns in this industry is processing uniformity, which is related to plasma uniformity across the wafer surface in both the radial and azimuthal directions [2]. For a cylindrical ICP, researchers often prioritize radial plasma uniformity [3,4], as plasma is generally assumed to be uniform in the azimuthal direction owing to the axial symmetry of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Inductively coupled plasmas (ICPs) are widely used in the semiconductor industry [1]. One of the most important concerns in this industry is processing uniformity, which is related to plasma uniformity across the wafer surface in both the radial and azimuthal directions [2]. For a cylindrical ICP, researchers often prioritize radial plasma uniformity [3,4], as plasma is generally assumed to be uniform in the azimuthal direction owing to the axial symmetry of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…During low-pressure operation (sub-Pa level), it was found that directional etching was achieved with reduced reactive ion etching (RIE) lag and critical dimension (CD) bias. Recently, good uniformity was confirmed in 450 mm wafer etching processes (5). In the 1980s and 1990s, a number of sophisticated etching functions were investigated, including gas pulsing (6), pulsed discharge (7), wafer radio-frequency (RF) pulsing (8,9), atomic layer control (10,11), and electron beam plasma (12).…”
Section: Introductionmentioning
confidence: 99%